2007
DOI: 10.1021/pr700606w
|View full text |Cite
|
Sign up to set email alerts
|

Application of Proteomics in the Discovery of Candidate Protein Biomarkers in a Diabetes Autoantibody Standardization Program Sample Subset

Abstract: Novel biomarkers of type 1 diabetes must be identified and validated in initial, exploratory studies before they can be assessed in proficiency evaluations. Currently, untargeted "-omics" approaches are under-utilized in profiling studies of clinical samples. This report describes the evaluation of capillary liquid chromatography (LC) coupled with mass spectrometry (MS) in a pilot proteomic analysis of human plasma and serum from a subset of control and type 1 diabetic individuals enrolled in the Diabetes Auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 44 publications
4
52
0
Order By: Relevance
“…Consistent with previous studies in children with overt type 1 diabetes, we found lower levels of APOA4 [19], APOC4 [19], CF3 [17,18], CF4 [17][18][19], clusterin [16,17], kininogen [17] and transthyretin [17] in children with islet autoantibodies. We also found lower levels of CF9 in autoantibodypositive children, while others [19] have reported slightly increased levels.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Consistent with previous studies in children with overt type 1 diabetes, we found lower levels of APOA4 [19], APOC4 [19], CF3 [17,18], CF4 [17][18][19], clusterin [16,17], kininogen [17] and transthyretin [17] in children with islet autoantibodies. We also found lower levels of CF9 in autoantibodypositive children, while others [19] have reported slightly increased levels.…”
Section: Discussionsupporting
confidence: 92%
“…2). Eight of those proteins (represented by 14 peptides) overlapped with findings from previous studies [16][17][18][19] (Table 1). This included four of the 14 peptides that were tested in our study because they had been identified in a previous study [17] (Table 1).…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…The diabetes dataset is based on frozen human serum samples from the DASP between 2000 and 2009 (Metz et al, 2008). The data consist of 10 healthy control subjects and 10 subjects with a recent diagnosis of type I diabetes mellitus.…”
Section: Datamentioning
confidence: 99%